Music at world's end three exiled musicians from Nazi Germany and Austria and their contribution to music in Iceland - Árni Heimir Ingólfsson 1973- (SUNY Press, 2025)
"A fascinating story of how three musicians, who escaped the Nazis, inspired Iceland's modern classical music."
SUNY Press = State University of New York Press
Keywords: Geschichte 1934-1974; Geschichte 1934-1945; Juden; Flucht; Drittes Reich; Musiker; Exil; Deutschland; Island; Österreich; Music / Iceland / 20th century / History and criticism; Exiles / Iceland / History / 20th century; Jewish musicians / Iceland / History / 20th century; Róbert Abraham Ottósson / 1912-1974; Edelstein, Heinz / 1902-1959; Urbancic, Victor